2017
DOI: 10.1142/s0192415x17500094
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Induces Beclin 1- and Extracellular Signal-Regulated Kinase-Dependent Autophagy in Ovarian Cancer Cells

Abstract: Baicalein (BA), one of the major compounds isolated from the root of Scutellaria baicalensis Gerogi, exhibits various pharmacological effects, such as anti-oxidant, anti-inflammatory, and anticancer effects. In this study, we found that BA reduced cell viability and increased apoptosis in ovarian cancer cells. Treatment of cells with BA enhanced microtubule-associated protein light chain 3-II (LC3-II) expression, acidic vesicular organelle and GFP-LC3 fluorescence dot accumulation. Combined treatment with chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…As a previous study reported that baicalein may regulate the ERK signaling pathway (24), the present study tested the effect of baicalein on the ERK signaling pathway and related proteins in HeLa cells. RT-qPCR results demonstrated that baicalein obviously declined ERK1/2, MMP2 and MMP9 levels in HeLa cells.…”
Section: Baicalein and U0126 Affected Erk Signaling Pathway And Apoptmentioning
confidence: 99%
“…As a previous study reported that baicalein may regulate the ERK signaling pathway (24), the present study tested the effect of baicalein on the ERK signaling pathway and related proteins in HeLa cells. RT-qPCR results demonstrated that baicalein obviously declined ERK1/2, MMP2 and MMP9 levels in HeLa cells.…”
Section: Baicalein and U0126 Affected Erk Signaling Pathway And Apoptmentioning
confidence: 99%
“…Baicalein (5, 6, 7-trihydroxyflavone) is a bioactive flavone, originally isolated from the roots of Scutellaria baicalensis and Scutellaria lateriflora which are traditionally used to treat various inflammatory diseases. In particular, it has been shown that baicalein the displays anticancer properties against various cancers such as pancreatic cancer (7,8), ovarian cancer (9), and gastric cancer (10) through the induction of cancer cell apoptosis, cell-cycle arrest, inhibition of angiogenesis, metastasis, and inflammation (11,12). Thus, baicalein has great potential as an agent for the treatment and prevention of cancer without causing severe side effects.…”
mentioning
confidence: 99%
“…Baicalein significantly increased the level of autophagy in cancer [35] and liver disease [36]. 6 However, other studies report that baicalein attenuated autophagy [37].…”
Section: Discussionmentioning
confidence: 92%